Differential expression of PKD1 and PKD2 in gastric cancer and analysis of PKD1 and PKD2 function in the model system - Shabelnik, M.Yu.; Kovalevska, L.M.; Yurchenko, M.Y.; Shlapatska, L.M.; Rzepetsky, Yu.; Sidorenko, S.P. (Experimental Oncology, 2011)
Aim: To study the differential expression of PKD1 and PKD2 in primary gastric cancer samples and to examine the role of PKD1 and PKD2 protein kinases in regulation of gastric tumor cell biology in the model system. Methods: Tumor samples of different histological variants of primary gastric cancer were analyzed. PKD1 and PKD2 expression levels in tumor samples were accessed by Western blot analysis and quantitative polymerase chain reaction (Q-PCR). As a model system we have used gastric adenocarcinoma сell line AGS sublines constitutively transfected by pcDNA3.1 coding PKD1 or PKD2, or empty pcDNA3.1 vector. These cell lines were analyzed by Western blot, Q-PCR, MTT and proliferation assays, in vitro scratch and Transwell assays, clonogenic assay. Results: It was found that primary gastric tumors possess different levels of PKD1 and PKD2 expression on mRNA and protein levels. Low level of PKD1 expression on protein and mRNA level was detected in low differentiated adenocarcinoma and ring cell gastric cancer — disorders with poor clinical prognosis. The high level of PKD2 expression was also found in gastric tumors with poor prognosis: low differentiated adenocarcinoma and adenogen cancer. To find out whether differential expression of PKD1 and PKD2 could affect biology of gastric tumor cells in vitro, we used a model system based on AGS cell line that constitutively expressed PKD1 or overexpressed PKD2. PKD1 transfection led to the inhibition of cell proliferation, migration and colony formation, in the meanwhile, the PKD2 overexpression enhanced proliferation, migration and colony formation capacities of AGS cells. Conclusions: Our data suggest that both downregulation of PKD1 or upregulation of PKD2 expression may determine the behavior of gastric tumor cells, which promotes invasive phenotype and could result in general poor prognosis.